A 3D-TTE left atrial function study in cardio-oncology patients. (14th October 2021) - Ferreira, V; Cruz Coutinho, M; Almeida Morais, L; Aguiar Rosa, S; Moura Branco, L; Galrinho, A; Timoteo, A T; Branco Mano, T; Cardoso, I; Castelo, A; Garcia Bras, P; Oliveira, S; et al.
Abstract: Introduction: Transthoracic Doppler echocardiography (TTE) remains the standard imaging method to evaluate cancer therapeutics-related cardiac dysfunction (CTRCD). 3D-TTE with strain analysis is a novel technique, proved useful for earlier detection of left ventricular (LV) function impairment. However, diastolic and left atrial (LA) function impact is less studied. Purpose: To assess LA volumetric and LA strain (LAS) features by 3D-TTE in cardio-oncology patients. Methods: A prospective study of female breast cancer patients (P) submitted to therapy (TH) who underwent serial monitoring by 2D and 3D-TTE. Standard 2D, 3D-TTE and LAS parameters were evaluated, including longitudinal (LALS) and circumferential strain (LACS) during conduit (cd), contraction (ct) and reservoir (r) phases. P were evaluated at T0, T1 and T2 (before, ≥6 and ≥12 months after starting TH). CTRCD was defined as an absolute decrease in 2D LVEF >10% to a value <54% or a relative decrease in 2D GLS >15%, according to literature. P with previous cancer treatment, coronary artery disease, significant valvular disease, and atrial arrhythmias were excluded. Results: 98 P (mean age 54.6±12.0 years-old), mostly treated with anthracyclines (78.6%, cumulative dose 268.2±77.6mg/m 2 ), anti-HER (70.4%) and radiotherapy (80.6%) were included. 2D LV and LA volumes had a significantly raise from baseline to T1 (2D LVEDV 82.2±18.8 vs 91.9±18.8 mL, p=0.019 and LA 43.3±12.9 vs 49.8±13.3 mL, p=0.005). 2D and 3D LVEF were significantly reduced during TH, however remaining within the limits of normality. 2D GLS was also impaired at T1 (−19.9±2.6% vs −18.6±3.1%, p=0.009). During a mean follow-up of 14.1±8.1months, 31 P (31.6%) developed CTRCD. 3D LV and LA volumes also globally increased at T1 comparing to baseline with partially recovery at T2. Maximum LA volume was significantly higher at T1 (39.1±9.3 vs 43.6±10.6 ml, p=0.024). 3D LA ejection fraction (T0 53.7±9.7%, T1 53.4±8.6%, T2 49.9±8.6%, pT0-T2=0.039) and LAS values tended to progressively worse during TH. LA dilation (vol>34ml/m 2 ) at baseline was correlated to dysfunction in contraction phase at T1 (LACSct −19.6±8.6 vs −17.3±4.6%, p=0.024). LACSr has substantially decreased from baseline to T2 (31.4±11.6 vs 27.0±10.4%, p=0.05). In univariate analysis, delta LALSr (T1-T0) was a predictor of CTRCD (mean −5.2% vs 1.9%, p=0.05). Conclusion: CTRCD was frequent during the earlier phase of breast cancer treatment. LA function was also affected, mirroring LV volumetric and functional changes. Diastolic dysfunction, assessed through LA reservoir strain, was impaired in association with CTRCD. 3D-TTE usefulness in the surveillance and monitoring of CTRCD goes beyond systolic LV function assessment, allowing a detailed LA function analysis. Funding Acknowledgement: Type of funding sources: None.